Projection Profiling: A Data Compressing Strategy in Three-Dimensional Liquid Chromatography for Quality Control of Traditional Herbal Medicine - Zhang, Jing (Sensors (Basel, Switzerland), 2025)
Chromatographic fingerprint technology has become the standard of quality control for traditional herbal medicines (THMs). But several issues are associated with the wavelength selection of the representative fingerprint, such as contradictory evaluation results at different wavelengths and the accurate quantification of each composition at one wavelength. These problems can be addressed by projection profiling. Projection profiling is a collection of all sample compositions at the maximum absorption wavelength after baseline correction. In this paper, eleven baseline correction algorithms are optimized by using the effective information factor (EI) as an indicator. The influence of different integration methods and wavelengths on analytical method validation and similarity analysis results are discussed in detail to clarify the advantages of the projection profiling. A total of 33 batches of Compound Licorice Tablets (CLTs) were used to show the influence of different wavelengths in a similarity evaluation. The results show that projection profiling is a better choice than any chromatogram at a certain wavelength, because projection profiling is more informative, accurate, and stable.